Mass Mortality Events of Invasive Freshwater Bivalves: Current Understanding and Potential Directions for Future Research - McDowell, William G.; Sousa, Ronaldo (Frontiers in Ecology and Evolution, 2019)
Mass mortality events, the rapid, catastrophic die-off of organisms, have recently been recognized as important events in controlling population size, but are difficult to quantify given their infrequency. These events can lead to large inputs of animal carcasses into aquatic ecosystems, which can have large ecosystem scale impacts. Invasive freshwater bivalves such as the Asian clam Corbicula fluminea, the zebra mussel Dreissena polymorpha, the golden mussel Limnoperna fortunei, and the Chinese pond mussel Sinanodonta woodiana can attain high densities and biomass and play important roles in aquatic ecosystems through filtration, bioturbation, and excretion. Invasive bivalve species can best be described as R-selected species and appear not to have the same tolerance to abiotic stressors as native species, causing them to be prone to mass mortality events in their invasive range. In contrast to their ecological effects while alive, the frequency and impacts of mass mortality events of invasive freshwater bivalves are not well understood. Here we review the causes and impacts of mass mortality events, as well as identify important questions for future research. Extreme abiotic conditions, including both drought and flooding, as well as high and low temperatures were the primary drivers of mass mortality events. Short-term impacts of mass mortality events include large pulses of nitrogen and increased oxygen stress due to large amounts of soft tissue decomposition, while shells can impact habitat availability and nutrient cycling for decades. Impacts on biological communities (bacteria, fungi, and macroinvertebrates) are less studied but some examples exist concerning C. fluminea. Better documentation of mass mortality events, particularly their magnitude and frequency, is needed to fully understand the impacts invasive bivalve species have on aquatic ecosystems, especially as climate change may make mass mortality events more frequent and/or have a larger magnitude.